Effectiveness of the Use of Digital Technology in Educational Activities by the Future Informatics Teacher - Eshaliev O‘tkir Soatmurodovich (Research Parks Publishers, 2023)
To increase the priorities of the development of the educational process in the higher education system of the Republic through the use of digital technologies and the effective organization of lessons. The article also highlights the importance of the introduction of digital technologies in higher education in the field of education through the study, systematization and generalization of existing practices in drawing scientifically sound conclusions.